Integrated Stress Response as a Therapeutic Target for CNS Injuries. (27th April 2017) - Romero-Ramírez, Lorenzo; Nieto-Sampedro, Manuel; Barreda-Manso, M. Asunción
Abstract : Central nervous system (CNS) injuries, caused by cerebrovascular pathologies or mechanical contusions (e.g., traumatic brain injury, TBI) comprise a diverse group of disorders that share the activation of the integrated stress response (ISR). This pathway is an innate protective mechanism, with encouraging potential as therapeutic target for CNS injury repair. In this review, we will focus on the progress in understanding the role of the ISR and we will discuss the effects of various small molecules that target the ISR on different animal models of CNS injury.